(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The woman represents the symbol of nature. She contributes to making progress in the family, society, and country through her active participation, the same as her male counterpart. But woman is suppressed into a lower status compared to the male power and position in the society intentionally, even after her great contribution in reality. This paper looks at how the inner world of women appears in selected novels by Indian English writer Anita Desai and African American author Toni Morrison. It focuses on Desai’s Cry, the Peacock, Bye-Bye Blackbird, and Where Shall We Go This Summer? As well as Morrison’s The Bluest Eye, Sula, and Beloved, women are a prime focus. In Anita Desai’s major novels, she depicts the world of heroines. They may be aloof, educated, sensitive, and faced psychological issues, racism, slave encounters, and emotional challenges in the insensitive world around them. Toni Morrison was always concerned about the unique position of Black women in American literature. She presents inner feelings of man-woman relationships, marital disharmony, character development, and themes such as abnormal psychology, identity, and resilience. The findings reveal a universal yet culturally distinct representation of women’s inner experiences in both authors’ works, providing important insights for feminist literary studies.